Pengaruh Self Efficacy, Motivasi, Kompensasi, dan Kepuasan Kerja Terhadap Kinerja Karyawan - Dian Nur Aprilia (Jurnal Manajemen Bisnis Eka Prasetya, 2021)
This paper will discuss the effect of work motivation for the performance of the Gunungkidul Regional Secretariat staff. The purpose of These papers are: 1. Does self-efficacy affect employee performance? 2. Does motivation affect employee performance? 3. Does Compensation affect employee performance? 4. Does job satisfaction affect employee performance? 5. Do the variables of self-efficacy (X1), motivation (X2), compensation (X3) and job satisfaction (X4) simultaneously affect employee performance (Y)? Gunungkidul Regional Secretariat and The population is 80 all employees at the Gunungkidul Regional Secretariat. Total sample 80 respondents were taken using the accidental sampling technique method. Data analyzed using multiple linear regression. The results obtained by Self efficacy have a positive effect on employee performance. Motivation has a positive effect on employee performance Compensation has a positive effect on employee performance Job satisfaction has a positive effect on employee performance Self-efficacy, motivation, compensation and job satisfaction simultaneously influence employee performance. Testing together, which shows the coefficient of determination of 0.753 equals 75.3%. While the rest (100% -75.3% = 24.7%) is influenced by other variables outside this regression equation or variables not examined. Keywords: , , , , employee performance.